2022
DOI: 10.1039/d1fo03816h
|View full text |Cite
|
Sign up to set email alerts
|

Insights from multi-spectroscopic analysis and molecular modeling to understand the structure–affinity relationship and the interaction mechanism of flavonoids with gliadin

Abstract: Gliadin, as a main composition of wheat storage protein, is used as drug encapsulation and delivery system owing to its specific characteristics. Flavonoids are regarded as active natural products with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The H 0 results showed that the addition of ILs could increase the H 0 of ΔLdcEt3 to some extent, and the H 0 values of both ΔLdcEt3-[Emim]Cl ( H 0 = 232.89) and ΔLdcEt3-[Ch]­[Ser] ( H 0 = 223.2) were improved compared to ΔLdcEt3 ( H 0 = 214.47) (Figure S42). The increase in H 0 meant that there were some internal hydrophobic residues/domains exposed in the external solution environment, , and the addition of ILs affected the surface properties of the protein. Therefore, the H 0 results demonstrated that the addition of ILs could change the microenvironment on the protein surface and affect the local structure of ΔLdcEt3, which might be in favor of the binding process of PLP and l -lysine.…”
Section: Resultsmentioning
confidence: 99%
“…The H 0 results showed that the addition of ILs could increase the H 0 of ΔLdcEt3 to some extent, and the H 0 values of both ΔLdcEt3-[Emim]Cl ( H 0 = 232.89) and ΔLdcEt3-[Ch]­[Ser] ( H 0 = 223.2) were improved compared to ΔLdcEt3 ( H 0 = 214.47) (Figure S42). The increase in H 0 meant that there were some internal hydrophobic residues/domains exposed in the external solution environment, , and the addition of ILs affected the surface properties of the protein. Therefore, the H 0 results demonstrated that the addition of ILs could change the microenvironment on the protein surface and affect the local structure of ΔLdcEt3, which might be in favor of the binding process of PLP and l -lysine.…”
Section: Resultsmentioning
confidence: 99%